Review Of The Implementation Of Inventory Accounting Systems By Per-02-Bc-2019 In Receiver Facilities Impor The Purpose Of Export (KITE) - Andi Yudha Amwilla P; Muanas HB (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2020)
Ease of Import for Export Purposes (KITE) is a government facility to export growth by manufacturing companies. Given this facility, of course, through several conditions that must be met, including the Inventory Information System model owned by the company that must be computerized and accessed by Customs and Excise as required in Per-02 / BC / 2019. This study aims to examine the suitability of the inventory information system owned by the company receiving the facility (KITE ), which is PT Batara Indah. PT Batara Indah registered as one of the companies using the KITE facility since 2014. The research method used is the descriptive qualitative method through document study. Information gathering is done through desk studies and discussions with related parties in the company. The results showed that PT Batara Indah had implemented an Integrated Inventory Accounting Information System model. If referring to the expected Directorate General of Customs and Excise regulation, PT Batara Indah has complied with the law.